Negocjowanie form i znaczeń podczas lekcji języka obcego — wyniki badań - Pawlak, Mirosław (Neofilolog, 2026)
According to numerous theorists and researchers, negotiation of form and meaning plays a crucial role in second and foreign language acquisition, since it enhances the quality of the input to which learners are exposed, it promotes noticing gaps and holes in their target language knowledge, and it provides them with opportunities to modify their incorrect output. Such advantages have been posited, among others, by the Noticing Hypothesis (Schmidt, 1990), the Interaction Hypothesis (Long, 1996) and the Output Hypothesis (Swain, 1995), and they have corroborated by the latest findings of research seeking to determine the value of different focus-on-form options and in particular different ways of providing corrective feedback (Sheen i Ellis, 2011; Pawlak, 2012). It can thus be assumed that teachers should stimulate the use of negotiation, either by reacting in the right way to learners' problematic utterances, planning communicative tasks encouraging its use, or undertaking training in this area. In line with such reasoning, the aim of this paper is to report the results of a study which attempted to determine the incidence of negotiated interaction in pair and group work activities, and to appraise its value for language acquisition.